ICSI outcomes of fresh or cryopreserved spermatozoa from micro-TESE in patients with nonobstructive azoospermia: CONSORT. Issue 12 (26th March 2021) - Zhang, Zhihong; Jing, Jili; Luo, Lili; Li, Leilei; Zhang, Hongyang; Xi, Qi; Liu, Ruizhi
Abstract : Abstract: The aim of this study was to evaluate intracytoplasmic sperm injection (ICSI) outcomes of fresh and cryopreserved sperm via microdissection testicular sperm extraction (micro-TESE) in patients with nonobstructive azoospermia (NOA). From March 2016 to February 2020, a total of 244 men with NOA underwent micro-TESE at the Center for Reproductive Medicine, First Hospital of Jilin University, P. R. China. These cases included 40 patients who underwent 40 ICSI cycles with fresh spermatozoa from micro-TESE (Group A) and 30 patients who underwent 30 ICSI cycles with cryopreserved spermatozoa from micro-TESE (Group B). The characteristics, embryonic development, and ICSI outcomes of patients were compared between groups A and B. Our sperm retrieval rate (SRR) by micro-TESE in patients with NOA was 35.25%. No statistical differences in the patient characteristics and fertilization or quality embryo rates were observed between Groups A and B. Higher miscarriage rates and lower live births were observed in Group B than in Group A (both P < .05). Fresh testicular spermatozoa seem to produce better ICSI outcomes than cryopreserved testicular spermatozoa from patients with NOA in the micro-TESE-ICSI cycle.